Analysis of Brexit and its policy lessons for Asian integration - Donghyun Park; Cynthia Castillejos-Petalcorin; Jungsuk Kim (Asian Development Bank Institute (ADBI), 2020)
Galvanized by the devastation of the Second World War, European countries achieved a historically unprecedented and unparalleled level of regional economic integration in the postwar period. Intensive cooperation between the two biggest powers of continental Western Europe, France, and Germany, lay at the core of Europe's seemingly relentless momentum toward integration, which the European Union (EU) crystallized. The French-German alliance also provided strong leadership and a sense of direction for the EU, which gained further traction with the admission of Central and Eastern European states after the fall of communism and the establishment of a monetary union among some of its members. However, more recently, the European integration process has no longer seemed to be unstoppable or inevitable. Most shockingly, the United Kingdom, a core EU member and the EU's third-largest economy, has opted to leave the union, triggering the Brexit process. Brexit is not the only sign of growing fractures within the EU. The current standoff between the EU and Italy over Italy's unwillingness to rein in its fiscal deficit is just one additional example of the loss of momentum. Our central objective is to examine the EU's past success and current problems from the perspective of Asian countries, in particular the ASEAN+3 countries, which have achieved some measure of integration, albeit well below that of the EU. It is important to note that both past success and current problems hold valuable lessons for the ASEAN+3 countries as they chart their own course toward regional integration. Given that the level of integration among the ASEAN+3 countries is much lower than that in the EU, it would be unwise to draw lessons, both positive and negative, without the proper context. Nevertheless, the European experience can still provide valuable insights for Asia's integration process.
Keywords: F02; F15; F40; F50; 330; regional integration; Asia; ASEAN; ASEAN+3; Europe; European Union; Brexit; United Kingdom